Views Of Elementary Education Programme Members on The Impact of Resource Use on Student Performance - Khaldi Rehman , (Spectrum of Engineering Sciences, 2024)
In tandem with the rapid speed of technological innovation, the incorporation of technology into educational settings is also accelerating. For the purpose of enhancing students' performance and fostering the internalisation of content, it isbecoming increasingly necessary to make certain that students maintain their concentration on the topics that are being taught in the classroom. In order to determine the opinions of pre-service teachers regarding the influencethat projection and overhead projectors have as instructional instruments on student accomplishment, the purpose of this research project was to conduct an investigation. A total of 184 senior pre-service teachers participated in the survey. Of them, 36 werefrom the social studies teaching department, 70 were from the science teachingdepartment, and 46 were from the pre-school teaching department. For the purposeof the study, the data obtained from the questionnaire were analysed with the use of the SPSS software programme. A t-test that was independent was utilised in order toascertain whether or not there is a significant connection between the responses of pre-service teachers and their gender and origin. In addition, a one-way analysis of variance (ANOVA) was carried out in order to determine whether or not there is asignificant connection between the responses of student instructors andthedepartments in which they are employed. It was discovered that the learning effectsof using an overhead projector were inconsistent when compared to the effects of using a projector. In accordance with the findings of the study, students have the perception that theutilisation of a projector and an overhead projector contributes to the improvement of education by adding diversity and reducing monotony. Additionally, it helps togenerate a learning atmosphere that is lively, pleasant, and user-friendly thanks toitscontribution. Key Words: Teaching Technologies, Use of Material, Overhead Projector andProjector, Student Attitudes, TTest, One-Way ANOVA